Institutional quality, financial development and inclusive growth: Asymmetric cointegration approach - Olumuyiwa Ganiyu Yinusa; Olalekan Bashir Aworinde; Ibrahim Abidemi Odusanya (International Journal of Management, Economics and Social Sciences (IJMESS), 2020)
The study examined the nexus between institutional quality, financial development and inclusive growth in Nigeria for the period 1984-2017. The study employed asymmetric cointegration approach to study the long-run relationship of institutional quality, financial development and inclusive growth in Nigeria. The results of the study showed that there is a long-run relationship between institutional quality, financial development and inclusive growth in Nigeria. It was also found that adjustments process to equilibrium for institutional quality, financial development and inclusive growth were asymmetric in Nigeria. The study therefore concludes that institutional quality and financial development are crucial variables that influence inclusive growth in Nigeria.
Keywords: C20; N2; O43; 330; Finance-growth link; institutional quality; financial development; inclusive growth; asymmetric cointegration